THE The efficacy of oral cyclosporine in a patient with drug reaction with eosinophilia and systemic symptoms probably due to cefadroxil - Evanti, Annisa Marsha; Widhiati, Suci (Journal of Pakistan Association of Dermatologists, 2023)
Abstract Background: Drug Reaction with Eosinophilia and Systemic Symptom (DRESS) is a rare but potentially life-threatening adverse drug reaction. Antibiotics especially cephalosporin often cause DRESS. The gold standard for diagnosing DRESS is by RegiSCAR criteria. Systemic corticosteroid is the first line therapy of DRESS but in certain cases, steroid sparing agents such as cyclosporine can be used to reduce side effects and accelerate patient recovery. Case: A 36-years-old man admitted to Moewardi General Hospital, Surakarta with recalcitrant DRESS due to melena after treated with methylprednisolone 125 mg/day IV. He presented with itchy red patches three weeks after taking cefadroxil 500 mg twice daily. Dermatovenereological status showed generalized scally erythematous partially hyperpigmented patches. The regiSCAR obtained 6 points (definite) and was diagnosed with DRESS. After administered with methylprednisolone 93.75 mg/day IV tapering off followed by oral cyclosporine 100 mg twice a day in a week showed clinical and laboratory improvement on the seventh days after therapy. Discussion: Cyclosporine as an adjuvant therapy for recalcitrant treatment of DRESS showed good improvement. It can be considered in cases where systemic corticosteroids are contraindicated, inadequate response to conventional therapy or long-term use of corticosteroids. The use of cyclosporine 100 mg twice daily for one week can lower the dose of systemic corticosteroid, furthermore can decrease the potential adverse events. Conclusion: This case reports a man with recalcitrant DRESS. The patient was treated with methylprednisolone 93.75 mg/day IV tapering off followed by oral cyclosporine 100 mg twice a day in a week showed clinical and laboratory improvement. Keywords: cefadroxil, cyclosporine, DRESS